Institutional Synergy in Diffusion and Adoption of Agricultural Technology in Farming Communities in Bantul District, Daerah Istimewa Yogyakarta - Ismiasih, Ismiasih; Dinarti, Siwi Istiana; Afroda, Helmi (JSEP (Journal of Social and Agricultural Economics), 2023)
The process of diffusion and adoption of agricultural technology can be realized properly if it is supported by the synergy of agricultural institutions and from farming actors. The existence of farmer groups and farmer cooperatives as part of agricultural institutions that are under one roof, is an important forum for farmers in overcoming various problems. The aims of the research were to find out the synergy between agricultural institutions in the diffusion of agricultural technology in farming communities in Bantul Regency, DIY and to find out the level of adoption of agricultural technology by farming communities in Bantul Regency, DIY. The research method was carried out in a descriptive qualitative manner. Data was collected by interviewing cooperative management, farmer groups and farmers with the help of a questionnaire. Data were analyzed by rating scale. From the research results it is known that the diffusion of agricultural technological innovations is carried out in synergy and in stages from the government through the Ministry of Agriculture, the agricultural service, Bank Indonesia, universities, PPL to the management of farmer groups to be disseminated to members. Farmers' cooperatives function as providers of capital, infrastructure such as seeds, subsidized and non-subsidized fertilizers, pesticides and medicines. Meanwhile, farmer groups function as providers of labor and modern agricultural equipment. The level of farmer adoption of agricultural technological innovations is in the good category with a score of 78.